Recognizing 'ourselves' in media and communications research. (November 2016) - Mansell, Robin
In this article, I argue that interdisciplinarity in the media and communication field encourages a focus on why the media and communication matter. It helps to draw scholarly attention to the need for theory development and critical analysis of the material and symbolic facets of mediated communication. Interdisciplinarity offers a pathway for resisting the hegemony of disciplinary projects and this approach encourages reflexive engagement among scholars within the media and communication field and beyond. The interdisciplinary pathway differs from a disciplinary approach because it can be open and responsive to the lived problems and experiences of social actors, examined from a variety of theoretical standpoints. For this reason, the interdisciplinary approach to the field means that while there is a need for an orientation to the problems to be investigated, it does not need to own a set of 'disciplinary' problems.